2002
DOI: 10.1046/j.1525-1497.2002.10209.x
|View full text |Cite
|
Sign up to set email alerts
|

How are patients’ specific ambulatory care experiences related to trust, satisfaction, and considering changing physicians?

Abstract: CONTEXT: Few data are available regarding the consequences of patients' problems with interpersonal aspects of medical care. OBJECTIVE:To assess the relationships between outpatient problem experiences and patients' trust in their physicians, ratings of their physicians, and consideration of changing physicians. We classified as problem experiences patients' reports that their physician does not always 1) give them enough time to explain the reason for the visit, 2) give answers to questions that are understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(129 citation statements)
references
References 42 publications
10
113
0
6
Order By: Relevance
“…We found that the relationship with the primary care provider uniformly drove patients' overall care experience. While these findings are consistent with prior work, [23][24][25][26][27] what is unique to our study is the context in which this occurred. As practices adopt PCMH standards calling for team-based care and greater patient agency in decision-making and care management, what appears to matter almost exclusively to the patients is their relationship with their PCP.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the relationship with the primary care provider uniformly drove patients' overall care experience. While these findings are consistent with prior work, [23][24][25][26][27] what is unique to our study is the context in which this occurred. As practices adopt PCMH standards calling for team-based care and greater patient agency in decision-making and care management, what appears to matter almost exclusively to the patients is their relationship with their PCP.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10][11] Thus, findings regarding racial differences in trust may contribute insight into racial disparities in health and health care. 12 While many studies have focused on the patientphysician relationship and attitudes toward health care, [12][13][14] little work has been done to investigate racial differences in attitudes toward different components of health service delivery. We sought to examine differences between African Americans and whites in attitudes toward physicians, health insurance plans, and hospitals.…”
mentioning
confidence: 99%
“…When the Harvard Medical School surveyed more than 2,000 patients about their office visits, poor communication emerged as the most important factor affecting patients' trust in their doctors and as the most likely reason for dissatisfaction and cause for switching physicians [17]. The Harvard study, published in the Journal of General Internal Medicine, highlights a need that America's medical schools acknowledge: physicians need better communication skills.…”
Section: The Essential Role Of Communicationmentioning
confidence: 99%